PENGARUH KONSENTRASI SUKROSA DAN BUBUR BUAH METE TERHADAP KADAR VITAMIN C, TOTAL GULA, TOTAL SERAT PANGAN, DAN AKTIVITAS AIR SELAI METE - Abidin, Zainal -; Harini, Titik Sri (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
ABSTRACT This research aims to determine and obtain a combination of treatments of sucrose concentration and cashew fruit pulp on sugar content, vitamin C content, total fiber content and activity of water of cashew jam. The factor in this research is the combination of sucrose + cashew pulp (A) in making cashew jam. This research was designed with 5 (five) treatment combinations of sucrose concentration and cashew pulp, namely: A1 = 45% sucrose + 55% cashew pulp, A2 = 50% sucrose + 50% cashew pulp, A3 = 55 sucrose + 45% pulp cashew pulp, A4 = 60% sucrose + 40% cashew pulp, A5 = 65% sucrose + 35% cashew pulp. The variables observed were vitamin C content, total sugar content, total fiber content and activity of water (Aw). The research data were analyzed using descriptive statistical methods which included mean and standard deviation or standard error/SE. The research results obtained were the highest vitamin C content: 154.142 ± 2.692 mg in treatment A1 (45% sucrose + 55% cashew pulp), the highest sugar content: 76.843 ± 0.103% in treatment A5 (65% sucrose + 35% cashew pulp ), the highest total dietary fiber content: 2.199 ± 0.029% in treatment A1 (45% sucrose + 55% cashew pulp) and the lowest activity of water: 0.745 ± 0.014 in treatment A5 (65% sucrose + 35% cashew pulp). Keywords: cashew; sucrose; jam